Stabilitas Fisik Transethosome Kurkumin yang Menggunakan Kombinasi Surfaktan Tween 60 dan Span 60 - Yudi Srifiana; Anisa Amalia; Yusnia Yusnia (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Curcumin has low solubility in water and has low stability so that a drug delivery system is needed that can overcome these problems. One delivery system that can be used to overcome these problems is transethosome. Transethosome is composed of several component, one of them is surfactant. Surfactant is a component that can help improve the stability of the transethosome system so that in this study research was conducted on the eff ect of the use of a combination of surfactants (tween 60 and span 60) on the physical stability of transethosome curcumin. In this study used a combination of tween 60 and span 60 with a ratio of 1: 2, 1: 1, 2: 1 at a concentration of 5%. Transethosome formed then characterized include organoleptic, viscosity, particle size and particle size distribution, zeta potential, adsorption effi ciency and pH. Transethosome characteristics were observed for 8 weeks to see the physical stability of the transethosome. The results at week 0 indicate that the transethosome formed a suspension with orange color and smelled of phosphatidylcholine with the highest viscosity in formula 3, has a particle size of 1-1000 nm, polydispersity 0-0.571, has a negative zeta potential value, has an absorption effi ciency above 80 % and pH 8.5-10.0. Physical stability test results show the use of a combination of tween 60 and span 60 with rasio 3:1 (F3) can improve the physical stability of transethosome curcumin.